2016
DOI: 10.1007/s10620-016-4155-9
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of the Microbiome in Barrett’s Esophagus and Esophageal Adenocarcinoma

Abstract: Esophageal adenocarcinoma and its precursor Barrett's esophagus have been rapidly increasing in incidence for half a century, for reasons not adequately explained by currently identified risk factors such as gastroesophageal reflux disease and obesity. The upper gastrointestinal microbiome may represent another potential cofactor. The distal esophagus has a distinct microbiome of predominantly oral-derived flora, which is altered in Barrett's esophagus and reflux esophagitis. Chronic low grade inflammation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 71 publications
0
56
0
2
Order By: Relevance
“…Changes in the composition of esophageal microorganisms can damage the esophageal mucosal barrier, leading to mucosal inflammation and persistent disease . Although we found that the composition of esophageal microbiota differed between controls and patients with RE, we were unable to determine the causal relationship between changes in the microbiota composition and RE …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Changes in the composition of esophageal microorganisms can damage the esophageal mucosal barrier, leading to mucosal inflammation and persistent disease . Although we found that the composition of esophageal microbiota differed between controls and patients with RE, we were unable to determine the causal relationship between changes in the microbiota composition and RE …”
Section: Discussionmentioning
confidence: 71%
“…9,10 Although we found that the composition of esophageal microbiota differed between controls and patients with RE, we were unable to determine the causal relationship between changes in the microbiota composition and RE. 25 Research has suggested that a high prevalence of Helicobacter pylori (H. pylori) infection in Asians could protect them against GERD. 26 The protective effects of H. pylori infection may be related to its negative effect on the secretion of gastric acid and the production of ghrelin, a hormone in the gastrointestinal tract that stimulates appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal adenocarcinoma (EAC) has increased greater than 10‐fold over recent decades . Unfortunately, the overall 5‐year survival of patients with EAC is below 19%, with most tumors discovered in advanced stages, after local invasion and/or metastasis occurred .…”
Section: Introductionmentioning
confidence: 99%
“…Esophageal adenocarcinoma (EAC) has increased greater than 10‐fold over recent decades . Unfortunately, the overall 5‐year survival of patients with EAC is below 19%, with most tumors discovered in advanced stages, after local invasion and/or metastasis occurred . Most EACs arise in patients with Barrett's esophagus (BE), which is characterized by replacement of the normal squamous esophageal mucosa by columnar epithelium with intestinal metaplasia (IM) and may subsequently progress to dysplasia and adenocarcinoma (DAC), through progressive development of low‐grade dysplasia (LGD), high‐grade dysplasia (HGD), intramucosal adenocarcinoma and advanced adenocarcinoma …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation